Direct laser writing of submicron photonic arrays for vapor-responsive sensing - Bradley, Louise; Delaney, Colm (My University, 2022)
A two photon polymerization technique was used to fabricate 2D photonic crystals based on a vapor-responsive hydrogel. By testing their vapor sensing performance, these photonic arrays were found to exhibit dynamic stimulus responses and show excellent structural and color reversibility.
Optica Advanced materials Congress
PUBLISHED
Maastricht,Limburg Netherlands
Keywords: polymerization; Photonic crystal sensors; Photonic crystals